2017
DOI: 10.1007/s11095-017-2210-7
|View full text |Cite
|
Sign up to set email alerts
|

Small Airway Absorption and Microdosimetry of Inhaled Corticosteroid Particles after Deposition

Abstract: Purpose To predict the cellular-level epithelial absorbed dose from deposited inhaled corticosteroid (ICS) particles in a model of an expanding and contracting small airway segment for different particle forms. Methods A computational fluid dynamics (CFD)-based model of drug dissolution, absorption and clearance occurring in the surface liquid of a representative small airway generation (G13) was developed and used to evaluate epithelial dose for the same deposited drug mass of conventional microparticles, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 90 publications
(118 reference statements)
0
16
0
Order By: Relevance
“…Additionally, it has been reported that the engineered particles with a geometric diameter greater than 10 microns can extend drug retention time in the lungs due to the ability of the deposited particles to escape from macrophage phagocytosis [ 29 ]. According to a recent study by Longest et al, computational models demonstrated that nanoaggregates are favorable for higher drug absorption efficiency and dose uniformity in the lungs, compared to microparticles [ 30 ]. Furthermore, TFF can produce amorphous high-surface area powders with submicron primary particles, which can enhance the dissolution rate and subsequently improve the bioavailability of poorly water-soluble drugs like remdesivir in the lungs [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it has been reported that the engineered particles with a geometric diameter greater than 10 microns can extend drug retention time in the lungs due to the ability of the deposited particles to escape from macrophage phagocytosis [ 29 ]. According to a recent study by Longest et al, computational models demonstrated that nanoaggregates are favorable for higher drug absorption efficiency and dose uniformity in the lungs, compared to microparticles [ 30 ]. Furthermore, TFF can produce amorphous high-surface area powders with submicron primary particles, which can enhance the dissolution rate and subsequently improve the bioavailability of poorly water-soluble drugs like remdesivir in the lungs [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it has been reported that the engineered particles with a geometric diameter greater than 10 microns can extend drug retention time in the lungs due to the ability of the deposited particles to escape from macrophage phagocytosis [28]. According to a recent study by Longest et al, computational models demonstrated that nanoaggregates are favorable for higher drug absorption efficiency and dose uniformity in the lungs, compared to microparticles [29]. Furthermore, TFF can produce amorphous high surface area powders with submicron primary particles, which can enhance the dissolution rate and subsequently improve the bioavailability of poorly water-soluble drugs like remdesivir in the lungs [30].…”
Section: Introductionmentioning
confidence: 99%
“…An important aspect of coupled CFD and PK modeling is where to switch from the 3D resolved CFD approach to mechanistic 1D models and/or PK rate equations. Based on the findings of Longest and Hindle [14], illustrated in Figure 5, we propose that CFD simulation all the way through epithelial cell absorption has important implications to bioavailability that cannot be captured with 1D approximations or PK rate equations. Therefore, when PK metrics such as plasma drug concentration are of interest, we recommend that the protocol implemented by Rygg et al [177] be followed in which the PK model is applied after epithelial cell absorption occurs with a 3D or other mechanistic model.…”
Section: Expert Opinionmentioning
confidence: 94%
“…Once inside the lung tissue, we view a PK model as valuable for determining tissue clearance and the prediction of plasma concentrations and distribution of drug throughout the body. Our assessment is that without CFD predictions through absorption, potentially important metrics such as the percentage of cells absorbing drug above a predefined threshold [14] cannot be accurately predicted.…”
Section: Expert Opinionmentioning
confidence: 99%
See 1 more Smart Citation